(untitled) (Texas Journal of Medical Science, 2024)
Viral infections can have significant repercussions on the human body, with the eyes being among the organs most susceptible to complications. Eye-related manifestations of viral infections range from mild irritation to severe vision impairment and blindness. This article delves into the side effects of various viral infections on the eye, including adenovirus, herpes simplex virus (HSV), varicella-zoster virus (VZV), cytomegalovirus (CMV), and emerging viruses like SARS-CoV-2. By analyzing clinical presentations, mechanisms of pathogenesis, and long-term effects, this study aims to raise awareness among healthcare professionals and inform future research. Preventive measures, early diagnosis, and treatment strategies are also discussed, highlighting the need for integrated approaches to managing ocular complications of viral diseases